Model and Implementation Of System Evolving Algorithm with Distributed Beginning Population - Tchórzewski, Jerzy (Studia Informatica. System and information technology, 2006)
This paper shows some results of using artificial intelligence methods for searching the new state of development system of electro energetic transmission network. In particular, is using evolving algorithm. Some experiments are prepared in MATLAB and Simulink environment.